CULTURA DE EXPANSÃO E DIFERENCIAÇÃO DE CÉLULAS -TRONCO PROVENIENTES DE TECIDOS ADIPOSOS HUMANOS - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2014)
The mesenchymal stem cells ( MSCs ) are a population of tissue -resident adult cells that have the capacity for self-renewal and differentiation into different cell types of mesenchymal origin with great potential for application in cell therapies. Thus the work proposed to obtain, expand and cultivation of MSCs from subcutaneous adipose tissue, visceral mesenteric and omental visceral taken from the same individual . The technique of mechanical dissociation was used, in order to investigate new sources for obtaining MSCs by this simple and cheap method. The samples were collected from patients undergoing bariatric surgery, between 30 to 45 years old, obese patients with associated diseases. Among 10 collected samples it was possible to measure cell viability from 4 patients. The tissue showed higher cell rate was the visceral tissue of omentum. In tests cryopreservation, the substance showed cryoprotectant capacity was 81% dimethylformamide at a concentration of 5% DMSO solution in a concentration of 5% 49% success was obtained.
Keywords: célula-tronco; tecido adiposo; diferenciação celular; stem cell; adipose tissue; cell differentiation; CNPQ::CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR